Bidirectional Modulation of Thermal and Chemical Sensitivity of trpm8 Channels by the Initial Region of the N-Terminal Domain - Madrid-Montecinos, R; Gonzalez-Figueroa, A; Pertusa-Pastor, M; Hardy-Traverso, P (American Society for Biochemistry and Molecular Biology Inc., 2014)
Background: The functional role of the TRPM8 N terminus remains poorly understood. Results: Truncation of the first 40 residues increases TRPM8 responses to cold and menthol, whereas deletions within the 40-60-residue region yield nonfunctional channels retained in the ER. Conclusion: Initial N terminus of TRPM8 is important for proper biogenesis and function. Significance: Variations within the N terminus can modulate thermal and chemical sensitivity of TRPM8. © 2014 by The American Society for Biochemistry and Molecular Biology, Inc.